The influence of digital culture, coordination and job satisfaction on employee performance with organizational commitment as a mediation variable - Pakpahan, Onny; Liswandi, Liswandi; Sudarmo, Agnes Puspitasari (Institute of Computer Science (IOCS), 2024)
Government organizations must always improve their performance according to the needs of a developing society. The survey results showed that the public did not get satisfaction so they got the highest